Dietary Supplements for Arthritis and other Inflammatory Conditions: Key Role of Mast Cells and Benefit of Combining Anti-Inflammatory and Proteoglycan Products - T. C. Theoharides (European Journal of Inflammation, 2003)
Arthritis is estimated to affect over 30% of all adults and all the available drugs add considerable morbidity and mortality of their own. A recent therapeutic approach targets the mast cells that are currently considered critical in a variety of inflammatory diseases, especially arthritis. Mast cells could be activated by many immune and neural triggers, as well as by many food substances and drugs leading to secretion of numerous vasoactive and inflammatory molecules. Recent studies have shown that mast cells can be inhibited by certain naturally occurring flavonoids, such as quercetin , and the sulfated proteoglycan chondroitin sulfate . Glucosamine and chondroitin are present in many dietary supplements, but neither the source nor the purity of the active substances is listed; moreover, these formulations do not permit sufficient absorption, due to the high molecular weight and negative charge. Moreover, a common source of chondroitin sulfate is cow trachea with the risk of spongioform encephalopathy (mad cow disease). A new series of dietary supplements (Algonot-Plus®) are based on published scientific evidence and combine quercetin, glucosamine sulfate and chondroitin sulfate of high purity in formulations that include kernel olive oil to increase absorption of the inhibitory substances.